Magma storage conditions beneath Krakatau, Indonesia: insight from geochemistry and rock magnetism studies - Pratama, Aditya; Nurfiani, Dini; Suryanata, Putu Billy; Ismail, Taufik; Bunga Naen, Gabriela Nogo Retnaningtyas; Abdurrachman, Mirzam; Supriyadi Banggur, Wilfridus Ferdinando; Asri, Nining Sumawati; Nareswari, Ratika Benita; Bijaksana, Satria; Hanif, Muhammad; Kriswati, Estu; et al. (Frontiers in Earth Science, 2023)
Krakatau volcano is characterized by cyclic phases of growth and destruction of the edifice. A volcanostratigraphic study identified three eruptive periods: Old Krakatau (OK), Young Krakatau (YK), and Anak Krakatau (AK). The OK and YK periods ended with the first and second caldera-forming eruptions (CFE) respectively. Due to its permanent activity and edifice evolution, Krakatau poses a high risk on the surrounding inhabited islands. Comprehensive characterization of eruptive products from all periods is fundamental to infer the evolution of magma storage conditions. We collected 16 lava and 5 pumice samples from and analyzed the samples using petromagnetic and geochemical approaches. The rock magnetic measurements reveal that OK and YK lavas have lower magnetic susceptibilities (χ LF ) than AK. The low values are a result of the presence of abundant Ti-titanomagnetite and ilmenite, whereas the only Fe-Ti oxide phase in the AK lavas is titanomagnetite, resulting in high χ LF . The YK pumice samples have the lowest χ LF due to the low abundance of Fe-Ti oxides. The petrological and geochemical analyses show that: 1) OK and YK magma storage regions are shallow (within the upper 3 km), contain more differentiated magmas, from which the OK magmas may be less oxidized and had lower temperatures than YK; 2) AK magma storage is deeper (up to 26 km), less differentiated, and erupted hotter but more reduced compared to OK and YK. We also relate the SiO 2 content of the samples and titanomagnetite chemistry to infer phases within a caldera cycle. The OK and YK lavas were the products of pre-CFE and their chemical characteristics are included at maturation phase, whereas the YK pumice samples were the product of the second CFE. Lastly, the post-second CFE activity of AK is currently in an incubation phase and represented by mafic products of frequent and small eruptions.